Loose fruit collector and instant packaging machine for palm oil industry / Akmal Lutfi Mohamad - Mohamad, Akmal Lutfi (2023)
This project is about to help Felda workers who has a hard time rearranging palm seeds as well as packaging it to send it to factories to make other products. Other than that, the palm seeds are small in size and amount are numerous to be picked up in a short period of time. The main objective for this project is to design and analyse Loose fruit collector and instant packaging procedure for it and also to fabricate physical prototype of this project. Methods that is used in this project rolling a collector roller along the earths floor and the roller will move along collecting the palm seeds in its way. At the end of this project, a new and fabricated design of a combination between a collector roller and a trolley. The trolley acts as a medium where the palm seeds are collected and will be packed from there. As for the collector roller it acts as a medium which collects the palm seeds. In the conclusion this project is medium on cost and is environmentally safe. It does not use any source of power or electricity. It works fully by human effort. The materials used are also easy to be found. The process to made this project is not complicated it involves cutting and joining process to connect each part.